Amulet / The Last Council, V.4 - Kibuishi, Kazu, 1978- (New York : Graphix, 2008)
After chasing the monster that kidnapped their mother, Emily and Navin find themselves in a magical world of man-eating demons and shadowy enemies, where they must learn to control an amulet given to them by their grandfather.
bk. 1. The stonekeeper -- bk. 2. The stonekeeper's curse -- bk. 3. The cloud searchers -- bk. 4. The last council
edited hb 2015-06-16
Keywords: Amulets -- Fiction; Brothers and sisters -- Fiction; Cartoons and comics; Fantasy; Comic books, strips, etc